Programa computacional para a avaliação da produtividade da mão de obra na execução de sistemas prediais - Nascimento, Thiago Augusto do (Universidade Federal de São Carlos, 2012)
The increased productivity of labor is an important factor for businesses in general face a scenario of competitiveness. In Construction there is a great opportunity for improving the productivity of labor and among the services that deserve attention in this issue, we highlight the implementation of Building Systems Hydraulic and Fuel Gas Piping (SPHSGC). However, few studies addressing the productivity of these systems have been conducted, mainly due to the difficulty of data collection, this difficulty compounded by the fact that its implementation be very fragmented, divided into several tasks and subtasks with different efforts, and happen simultaneously at different floors. In this context, justifies the development of a comptational tool that integrates the design of building systems, with the differential use graphical interface, procedures for data collection to assess the productivity of labor in the execution of these building systems, goal this work. To achieve it, initially proceeded to the understanding of the concept of productivity and indicators for its measurement as well as the procedures for collecting data in order to measure them, understanding the parts compose the SPHSGC and the process of implementation, evaluation and choice of programming language for the development of the software and ultimately their development, with testing to verify its applicability and reliability. As contributions stand out initially using the graphical interface of the projects of building systems to o stain quantitative data regarding the performance of these services, linking this information to the man-hours defendants, in their various tasks and subtasks involved in their implementation . Besides this factor facilitator, the program offers the user, which can be the manager of services or even responsible for implementation, indicators of productivity of labor and the current stage of its implementation over the floors of the building. Finally, it is noteworthy that the current use of this tool will provide managers with a database on the productivity of labor that can be used for prediction of these values for future works, feasibility study, correct sizing of work teams, lifting costs among other benefits.
Keywords: Produtividade da mão de obra; Banco de Dados; Sistemas Prediais; Productivity of manpower; Database; Building Systems; CIENCIAS EXATAS E DA TERRA